Potassium availability in relation to mineralogy in some floodplain soils of Bangladesh - Khan, ZH; Hussain, MS; Hassan, MM (Dhaka University Journal of Biological Sciences, 2013)
Abstract not available Dhaka Univ. J. Biol. Sci. 22(1): 79-83, 2013 (January)